Two new species of Acroceratitis Hendel (Diptera: Tephritidae) and an updated key for the species from India - David, K. J.; Hancock, D. L.; Ramani, S. (Zootaxa, 2014)
Two new species of genus Acroceratitis Hendel, namely A. parastriata David & Hancock , sp. nov. and A. breviscapa David, Ramani & Hancock, sp. nov., are described from India. A. histrionica (de Meijere) is recorded for the first time from India. An updated key to Indian species of Acroceratitis is also provided.